Weighted Pseudo Almost Periodic Solutions for a Class of Hematopoiesis Model with Time-Varying Delay - Hui Zhou;Liu Yang;Wei Jiang (分析理论与应用：英文刊, 2017)
In this paper, firstly, a notion of a class of generalized weighted pseudo al- most periodic function is introduced, then we investigate some basic and essential properties of the space that consists of these functions. Finally, we study the exis- tence of weighted pseudo almost periodic solutions to hematopoiesis model with time- varying delay.